Carbamazepine removal from low-strength municipal wastewater using a combined UASB-MBR treatment system - M. J. Moya-Llamas (IWA Publishing, 2021)
An Upflow Anaerobic Sludge Blanket reactor combined with a two-stage membrane bioreactor were operated for 193 days in order to evaluate the biological removal of carbamazepine (CBZ) from low-strength municipal wastewater. The system worked in three different organic load stages (0.7 ± 0.1 kg COD·m−3·d−1, 0.4 ± 0.1 kg COD·m−3·d−1 and 0.1 ± 0.0 kg COD·m−3·d−1) to assess the impact of the influent OLR on operational parameters such as anaerobic and aerobic sludge retention time (SRT), acidity, volatile fatty acids (VFAs), biomass activity or biogas production. The highest carbamazepine removals were achieved during the anaerobic stage (UASB reactor), reaching averages of 48.9%, 48.0% and 38.2% operating at high, medium and low OLR, respectively. The aerobic treatment (MBR) served as post-treatment, improving the removals, and the global UASB-MBR system reached averages of 70.0%, 59.6% and 49.8% when the influent was at medium and low OLR, respectively. The results demonstrate the potential of combined biological systems on the removal of recalcitrant pharmaceuticals. HIGHLIGHTS UASB-MBR was proposed for the removal of the anti-epileptic drug carbamazepine.; The CBZ removal rates of the UASB-MBR combined system were highly dependent on the organic loads of the influent.; UASB-MBR system proved to be particularly suitable for treating municipal wastewater containing CBZ at OLR above 0.7 kg COD·m−3·d−1.; UASB reactor was the main contributor to degradation of the pharmaceutical CBZ.;